Implications for bean breeders of studies on the origins of common beans, Phaseolus vulgaris L. - Debouck, Daniel G.; Tohme, Joseph M. (International Center for Tropical Agriculture, 1989)
Three lines of evidence (botanical, archaeological, and biochemical results) of multiple and independent domestication of wild populations of common beans in the Americas are revicwed. These domestication events took place at least 10,000 yr ago from different wild bean populations. In addition to a founder effect, a lower no. of populations could have been domesticated in Mesoamerica vs. the southern Andes. Some limitations related to the formation of gene pools and the uniformity of the selective pressures are discussed. Practical consequences for bean breeding related to the genetic incompatibility and a possible case of co- evolution are presented. (AS).